Biology of the Uterus 1977
DOI: 10.1007/978-1-4684-2271-9_9
|View full text |Cite
|
Sign up to set email alerts
|

The Implantation Reaction

Abstract: Implantation involves the attachment of the blastocyst to the wall of the uterus with, in some cases, the embedding of the entire ovum in the uterine wall. Associated with it are very profound and characteristic changes in the endometrium both during preparation for implantation and following attachment of the blastocyst. In this chapter, the uterine changes that take place during preparation will be considered first and then the changes during the process of implantation. The former occur regularly and freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
121
0
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 265 publications
(284 reference statements)
4
121
0
1
Order By: Relevance
“…In other situations, PAF has been implicated in many aspects of inflammation including the activation of platelets and leucocytes and the liberation of vasoactive substances such as prostaglandins. Since the response of the uterus to an implanting blastocyst appears to resemble an inflammatory-like reaction (Finn, 1977) and is characterized by an increase in vascular permeability (Psychoyos, 1961), some involvement of PAF would not be unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…In other situations, PAF has been implicated in many aspects of inflammation including the activation of platelets and leucocytes and the liberation of vasoactive substances such as prostaglandins. Since the response of the uterus to an implanting blastocyst appears to resemble an inflammatory-like reaction (Finn, 1977) and is characterized by an increase in vascular permeability (Psychoyos, 1961), some involvement of PAF would not be unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine weight increases dramatically during decidualization, due to hyperplasia and hyperproliferation of endometrial cells (Finn, 1977), and endometrial cells differentiate into enlarged decidual cells with large nuclei and increased chromatin surface, some of these cells being binucleate (Kennedy, 1986). Similar events can be induced in the rat uterus by local artificial stimuli, provided the stimulus is given when the uterus is most sensitive to deciduoma induction, at Day 5 of pseudopregnancy (De Feo, 1963).…”
Section: Introductionmentioning
confidence: 93%
“…Vitamin D3 metabolites or solvents were injected into the uterine lumen with a I-ml plastic syringe and a 16/5 mm needle (Terumo, Haaszode, Belgium) via the upper part of the left uterine horn. Care was taken not to alter the uterine wall, as it is well known that local injury of the uterine epithelium can by itself induce decidualization (De Feo, 1967;Finn, 1977). The caudal end of the uterus was not ligatured to avoid a stress-induced decidualization.…”
Section: Introductionmentioning
confidence: 99%
“…The role of progesterone (P) supplementation in the luteal phase of in vitro fertilization (IVF) cycles is well established worldwide [12], but the influence of the luteal phase E2 level on implantation is not clearly defined [13][14][15]. First Stewart et al revealed a significant difference in E2 levels between fertile and infertile cycles of fertile women who underwent donor insemination [16].…”
Section: Introductionmentioning
confidence: 99%